Rural Identity and Its Roles in Boosting Local Economic Sustainability in Nglanggeran Village of Yogyakarta - Ratna Eka Suminar; Sudaryono Sastrosasmito; Doddy Aditya Iskandar (Universitas Gadjah Mada, 2023)
Contemporary studies on rural areas often focus on rural areas' disadvantages and inabilities to accelerate economic growth and stimulate regional development. Within this dominant perspective, local identity or culture is often seen as obstacles to development. In contrast, this article unpacks how rural identity can develop the local economy and then achieve sustainability in a rural area, which allows us to situate the constructive roles of of rural community in regional development. Drawing from field observation and unstructured interviews with resource persons from Nglanggeran Village in Gunung Kidul Regency, Yogyakarta, we found a reciprocal relationship between rural identity and local economy, of which it forms and reinforces rural sustainability. Our findings emphasize the importance of creating rural identity-based policy to bolster regional economy and development.